Light energy distribution of submicron charged particles based on the scattering-enhancing effect. (April 2023) - Zhang, Siqi; Li, Ang; Wang, Jiaan; Du, Wenhan; Ren, Zhe; Yang, Xu; Rong, Zejun
Highlights: Scattering-enhancing effect can affect the light energy distribution. The effect can be reflected in the light energy received by the photodetector. Light energy distribution models for charged particles are established. The models are the necessary link between theoretical and practical measurements. Realize the forward deduction of light energy distribution for charged particles. Abstract: Magnetic microspheres, charged soot and other charged sub-micron particles are widely used, and the accurate measurement of their particle size is crucial to biomedical, environmental monitoring and other fields. During light scattering measurements, the light energy distribution projected onto each ring surface of the photodetector is the core data for particle size inversion calculations. When the measured particle is charged, the light energy distribution will be different from its neutral state due to the scattering-enhancing effect of surface charges. Therefore, it is necessary to confirm the extent of the scattering-enhancing effect on the light energy distribution by numerical simulation, before actual measurement. In this paper, calculation models of scattered light energy distribution are established for charged single particle, monodisperse particle system and polydisperse particle system respectively. Considering the difference between the complex refractive indices of charged particles, the forward scattering of silica and polystyrene with different monodisperse degrees are taken as an example to analyze the light energy distribution. The results show that the scattering-enhancing effect of surface charges can affect the light energy distribution of submicron particles, and the smaller the median diameter of the particle system and the lower the monodisperse degree, the more significant the effect is. At a median diameter of 0.1 μm, the light energy of charged particles with different monodisperse degrees increased by an average of about 3.5 times, near the scattering angle of 45° This research realizes the forward deduction of the light energy distribution for charged particles, and provides the necessary theoretical support for the visible light measurement of charged submicron and nanoparticles.